Penerapan Model Missouri Mathematics Project Terhadap Hasil Belajar Matematika - Kadek Suryati; Ni Wayan Suardiati Putri (UNIB Press, 2023)
Monotonous learning will make students passive and only recipients of concepts. The purpose of this research was to describe the learning model missouri mathematics project (MMP) in improving learning outcomes in computer mathematics courses.This research was carried out on campus Institut Bisnis dan Teknologi Indonesia (INSTIKI). The subjects in this study were first semester students majoring in Informatics Engineering Class C for the 2022/2023 school year has 30 students. Data collection methods used are interviews, observation, questionnaire and test methods. Data analysis technique using descriptive analysis. The results showed that the increase in mathematics learning outcomes for students majoring in informatics engineering from cycle I obtained an average score on the mathematics test of 67.23 with a total of 30 students taking the test. Of the 30 students, 21 students still scored in the poor category and 9 in the good category and increased in cycle II with an average score of 73.83 with 30 students taking the test. Of the 30 students, 18 students still got grades in the good category, 7 students got the fair category and 5 people in the less category. Whereas the results of student responses to the MMP learning model received a positive response of 80% and a negative response of 20%.